General anesthesia is an independent predictor for worse maternal outcome in pregnant pulmonary arterial hypertension patients without cardiac shunt but not for those with shunt - Weida Lu; Min Li; Fuqing Ji; Hua Feng; Liangyi Qie; Guo Li; Qiushang Ji; Mingying Ling; Fan Jiang; Xiaopei Cui (Emergency and Critical Care Medicine)
Abstract. Background. Although pregnancy imposes extra risk in patients with pulmonary arterial hypertension (PAH), hemodynamic characteristics vary between PAH patients with and without cardiac shunts. However, previous studies did not take hemodynamic differences in PAH patients into consideration for pregnancy outcome analysis. We aimed to identify predictors for peripartum outcome of PAH patients without/with cardiac shunt. Methods. We retrospectively analyzed the medical records of PAH gravidae parturiated by cesarean delivery (C-section) from 4 hospitals. Maternal death and major adverse cardiac events (MACEs) occurring during pregnancy or within 6 weeks postpartum were defined as composite end points. Risk factors for end points were analyzed separately in patients with and without cardiac shunt. The effect of general anesthesia on MACEs and maternal death was analyzed considering cardiac shunts. Results. One hundred and eighty-one PAH gravidae were included, of whom 85 had PAH without cardiac shunt and 96 with shunt. Patients who met combined end points were 19/85 in those without shunt compared with 23/96 in those with shunt. The mortality rates were 11.8% and 9.4%, respectively. Both World Health Organization functional class (WHO-FC) III/IV and general anesthesia were predictors for gravidae without shunt, whereas only WHO-FC III/IV was a predictor for gravidae with shunt. General anesthesia increased the MACE risk (odds ratio, 9.000; 95% confidence interval, 2.628–30.820) and maternal mortality (odds ratio, 11.000; 95% confidence interval, 2.595–46.622; P = 0.039) in patients without cardiac shunt but not in those with shunt during C-section. Conclusion. All PAH gravidae with WHO-FC III/IV are at high risk and should receive intensive care. General anesthesia should be avoided during C-section for PAH gravidae without a cardiac shunt.